Water Management in Agricultural Production, the Economy, and Venezuelan Society - Moreno-Pizani, Maria Alejandra (Frontiers in Sustainable Food Systems, 2021)
The availability of water resources has a direct impact on the economy of a country and the development of the main production processes, from agriculture, irrigation, and food production, to energy generation and water supply. The regional economic and social development is influenced by an adequate management of water resources because it stimulates the economy by expanding and ability to provide water for multiple uses, directly impacting on the generation of employment the improving the quality of life of the population. Venezuela has abundant surface water resources in the large basins. The northern part of Venezuela, where the highest percentage of the population and the main economic activities are based, face a severe water scarcity. Irrigation systems under public sector administration are characterized by large budgetary restrictions, with works for rehabilitation, operation, and maintenance generally carried out with inefficient results, due to lack of adequate technical supervision. There is a gap of official information that allows highlight the crisis that the agricultural sector has faced in the last decade. Another, very important aspect is Venezuela's severe energy crisis which began to present a deficit of electric power generation that has been alarmingly evident since 2009, which has worsened for more than a decade, causing the lack of electricity supply in large regions of the country for periods of time exceeding 100 h, contributing to aggravate the country's economic crisis. Due to the situation described, Venezuelan food systems have been seriously affected mainly by the advanced deterioration of irrigation infrastructure and the water availability on production processes. This paper explores and analyses the influence of water management on production Venezuelan economics and society, focus in three pillars representing the qualitative and quantitative relationships of water management and its impact on the system considering the aspects related to the sustainability of Venezuelan agri-food systems, analyzing the fundamental aspects for food production, main indicators related to the national economy, addressing the challenges to ensure food security.